Rasio lingkar pinggang pinggul dan rasio lingkar pinggang tinggi badan pada penderita hipertensi - Damayanti, Luthfiyah; Nugraha, Gaga Irawan; Ariyanto, Eko Fuji; Inayati, Iis; Ghozali, Mohammad; Fatimah, Siti Nur (Jurnal Gizi Klinik Indonesia, 2025)
Waist-hip ratio (WHR) and waist-height ratio (WHtR) in hypertension patientsBackground: Hypertension is a health problem characterized by systolic blood pressure ≥140 mmHg and/or diastolic pressure ≥90 mmHg. One risk factor for hypertension is central obesity, which can be indicated by the Waist-Hip Ratio (WHR) and Waist-Height Ratio (WHtR). Objective: This study aimed to determine WHR and WHtR in hypertensive patients. Methods: This research is a descriptive observational study with a cross-sectional approach, cross-tabulation, and Spearman analysis using secondary data in the form of hypertension patient data from the cardiometabolic working group study from January 2022 to July 2023 in Cibeber Village, which includes data on systolic and diastolic blood pressure, waist circumference, hip circumference, and body height. Consecutive sampling was used to obtain 173 subjects aged 46-65 years, comprising 116 women and 57 men. Results: Stage 1 hypertension was the most common category (38.7%). The average WHR is 0.90 (men) and 0.89 (women), while the average WHtR is 0.54 (men) and 0.59 (women). There are 134 subjects (77,5%) with high WHR and 147 subjects (85%) with high WHtR. The higher WHR and WHtR category was more frequently found in subjects with stage I hypertension. Conclusions: WHR and WHtR values above the cut-off are more common in subjects with hypertension.